UNDERSTANDING ISLAMIC JURISPRUDENCE AND ITS’ THEORY OF LAWMAKING - Kho Feng Ming (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The notion of jurisprudence is not an unfamiliar word to both Western and Islamic jurisdictions. Unlike the eternal riddle faced by the former, the latter focus on how the law is made from its’ Shari’ah sources. Rulings are laid down in the Holy Book of al-Qur’an, and transmitted to us via the Prophet p.b.u.h. These commands regulate the life of people, and is suitable to be applied in all ages. Progress of the society often accompanied by new arising problems. In solving new problems, certain principles are to be abide by the jurists. Using the methodology of analysis of archived materials, this paper intends to discuss the characteristics of Islamic jurisprudence, and its’ theory of lawmaking will be highlighted. The discussion is centered on how these rules are derived from the two most authoritative sources of Islamic law (al-Qur’an and Sunnah) today to solve new emerging problems. It is found that the whole system of Islamic law and Islamic jurisprudence is in a well-ordered manner, and is being able to be applied in any era. The rulings laid down in the al-Qur’an has certain legislative features, and its’ purpose behind it is to allow open area of lawmaking. It is perceived that Allah provides the opportunity for jurists of different era to exercise ijtihad to solve new arising problems, and it shall be done in accordance with the principles and rules laid down in the Qur’an and Sunnah of Prophet.